Ibrutinib: a paradigm shift in management of CLL. Issue 6 (December 2014) - Badar, Talha; Burger, Jan A; Wierda, William G; O'Brien, Susan
<x xml:space="preserve">Abstract</x> B-cell receptor (BCR) signaling plays a vital role in B-cell malignancies; Bruton tyrosine kinase is a critical mediator of this signaling. BCR signaling, either constitutively or following antigen binding, leads to activation of several downstream pathways involved in cell survival, proliferation and migration. The efficacy observed in studies of the Bruton tyrosine kinase inhibitor, ibrutinib, confirms that BCR signaling is critical for the growth of B-cell malignancies. Ibrutinib characteristically induces redistribution of malignant B cells from tissues into the peripheral blood and rapid resolution of adenopathy. Furthermore, ibrutinib therapy results in normalization of lymphocyte counts and improvement in cytopenias. Ibrutinib has been shown to have an excellent safety profile and does not cause myelosuppression. Early data from combination studies of ibrutinib with anti-CD20 monoclonal antibodies have shown more rapid responses compared to those seen with ibrutinib monotherapy. Current data strongly support continued clinical evaluation of ibrutinib in B-cell malignancies.